Decision making for transjugular intrahepatic portosystemic stent shunt in refractory ascites and variceal bleeding: MELD, or not MELD, that is the question. Issue Volume 33:Issue S1(2021) (20th November 2020) - Pitton, Michael B.; Zimmermann, Tim; Mildenberger, Philipp; Weinmann, Arndt; Kloeckner, Roman; Düber, Christoph; Mittler, Jens; Hoppe-Lotichius, Maria; Otto, Gerd
Abstract : Purpose: The model of end-stage liver disease (MELD) score has been shown to predict 3-month prognosis following transjugular intrahepatic portosystemic stent shunt (TIPS) in liver cirrhosis; however, that score was derived from a mixed cohort, including patients with refractory ascites and variceal bleeding. This study re-evaluates the role of the MELD score and focuses on differences between both groups of patients. Methods: A total of 301 patients (192 male and 109 female) received TIPS, 213 because of refractory ascites and 88 because of variceal bleeding. Univariate and multivariate Cox analyses were performed to identify predictors of mortality and area under the receiver operator characteristics (AUROC) were used to assess the prognostic capacity of the MELD score and of the results of predictors of the multivariate analyses. Results: In refractory ascites, age, bilirubin and albumin were independent predictors of mortality. In variceal bleeding, emergency TIPS during ongoing bleeding, concomitant grade III ascites, history of hepatic encephalopathy, spontaneous bacterial peritonitis, bilirubin and platelet count proved significant. AUROCs of the MELD score for 3-month survival yielded 0.543 and 0.836 for refractory ascites and variceal bleeding, respectively ( P  < 0.001). For 1-year survival, the respective AUROCs yielded 0.533 and 0.767 ( P  < 0.001). In contrast to MELD, the AUROCs based on the calculated risk scores of this study resulted in 0.660 and 0.876 for 3-month survival, and 0.665 and 0.835 for 1-year survival in patients with ascites and variceal bleeding, respectively. Conclusion: In refractory ascites, the prognostic capability of MELD is significantly inferior compared to variceal bleeding. The results of our multivariate analyses and AUROC calculations corroborate the impact of different prognostic variables in patients undergoing TIPS for ascites and variceal bleeding.